1996
DOI: 10.1042/bj3200293
|View full text |Cite
|
Sign up to set email alerts
|

Internalization and catabolism of radiolabelled antibodies to the MHC class-II invariant chain by B-cell lymphomas

Abstract: The fate of antibody (Ab) LL1, which reacts with the invariant chain (Ii) subunit of the immature MHC class-II antigen (CD74) after binding to the surface of B-cell lymphomas was investigated. This Ab was internalized and catabolized very rapidly, much faster than other Abs that are considered to be rapidly internalized, such as CD19, CD22 and anti-(transferrin receptor). Such internalization did not depend on Ab cross-linking. The capacity of this uptake process was determined in long-term experiments by incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 33 publications
(51 reference statements)
2
79
0
Order By: Relevance
“…If no clear match was found, partial or total manual de novo sequencing of the peptide was conducted and the search was repeated using the MSEdman program. After sequencing and source protein identification, an affinity peptide score was calculated for each peptide using a predictive matrix obtained by Hammer et al (27), by peptide side chain scanning techniques, based on the DR4 peptide-binding motif (26). A value higher than 2 was considered a high score, theoretically corresponding to high affinity binding.…”
Section: Peptide Sequencingmentioning
confidence: 99%
“…If no clear match was found, partial or total manual de novo sequencing of the peptide was conducted and the search was repeated using the MSEdman program. After sequencing and source protein identification, an affinity peptide score was calculated for each peptide using a predictive matrix obtained by Hammer et al (27), by peptide side chain scanning techniques, based on the DR4 peptide-binding motif (26). A value higher than 2 was considered a high score, theoretically corresponding to high affinity binding.…”
Section: Peptide Sequencingmentioning
confidence: 99%
“…Thus, CD74 internalization is highly dynamic, with the antibody being moved quickly from the surface and unloaded inside the cell, followed by CD74 reexpression on the surface. Fab' internalization occurs just as rapidly as immunoglobulin G (IgG) binding, indicating that bivalent binding is not required (3,10). Later studies with a complementarity-determining region (CDR)-grafted version of murine LL1, milatuzumab (hLL1), found that the antibody could alter B-cell proliferation, migration, and adhesion molecule expression (8,11,12), but the exceptional internalization properties of the anti-CD74 antibody made it an efficient carrier for the intracellular delivery of cancer therapeutics (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately, 80% of the CD74 on the cell surface is associated with the MHC II antigen, HLA-DR (3). Using the murine anti-CD74 antibody, LL1, the Raji Burkitt lymphoma cell line was estimated to have 4.8 Â 10 4 copies per cell, but because of rapid intracellular transit, approximately 8 Â 10 6 antibody molecules were internalized and catabolized per cell per day (10). Thus, CD74 internalization is highly dynamic, with the antibody being moved quickly from the surface and unloaded inside the cell, followed by CD74 reexpression on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The RL cell line, a diffuse, large cell B-lymphoma, was described previously [7], and is available from the American Type Culture Collection (ATCC, Manassas, VA, USA). Cells were cultured as described [7,8].…”
Section: Cell Lines Abs and Ab Conjugatesmentioning
confidence: 99%
“…Cells were cultured as described [7,8]. They were tested routinely for mycoplasma by the Mycotect assay (Life Technologies, Grand Island, NY, USA), and were negative.…”
Section: Cell Lines Abs and Ab Conjugatesmentioning
confidence: 99%